An exploration of factors affecting students’ studies in one selected university in Zimbabwe - Zikhali, Joyce; Chauraya, Efiritha; Madzanire, Daniel; Maphosa, Cosmas (Kamla - Raj, 2016)
Several issues promote or hinder students’ progress in pursuit of their studies. The present study sought to establish enabling and constraining factors to students’ academic progress in one selected state university in Zimbabwe. The study adopted a descriptive survey approach which utilized both qualitative and quantitative methodologies. Informed by Archer ’s theory on structure, culture and agency, the study collected data from students in five selected faculties in the one selected university. A convenient sample of one hundred and ten students participated in the study. A semi-structured questionnaire was used to collect both quantitative and qualitative data. Quantitative data were analysed with the aid of the Statistical Package for Social Sciences (SPSS) software package version 21. Qualitative data were analysed using content analysis method and presented through verbatim quotations of the respondents. The study found that academic overload, lack of time management, lack of requisite materials, computer illiteracy and financial problems negatively affected students’ studies while factors such as student accommodation, relationships and command of the language of instruction did not have much effect. The researchers conclude that there were structural, cultural and agential factors that negatively affected students’ studies. Recommendations are made in view of the major findings.